A new chromosomal rearrangement improves the adaptation of wine yeasts to sulfite. (25th March 2019) - García‐Ríos, Estéfani; Nuévalos, Marcos; Barrio, Eladio; Puig, Sergi; Guillamón, José M.
Summary: Sulfite‐generating compounds are widely used during winemaking as preservatives because of its antimicrobial and antioxidant properties. Thus, wine yeast strains have developed different genetic strategies to increase its sulfite resistance. The most efficient sulfite detoxification mechanism in Saccharomyces cerevisiae uses a plasma membrane protein called Ssu1 to efflux sulfite. In wine yeast strains, two chromosomal translocations (VIIItXVI and XVtXVI) involving the SSU1 promoter region have been shown to upregulate SSU1 expression and, as a result, increase sulfite tolerance. In this study, we have identified a novel chromosomal rearrangement that triggers wine yeast sulfite adaptation. An inversion in chromosome XVI (inv‐XVI) probably due to sequence microhomology, which involves SSU1 and GCR1 regulatory regions, increases the expression of SSU1 and the sulfite resistance of a commercial wine yeast strain. A detailed dissection of this chimeric SSU1 promoter indicates that both the removed SSU1 promoter sequence and the relocated GCR1 sequence contribute to SSU1 upregulation and sulfite tolerance. However, no relevant function has been attributed to the SSU1 ‐promoter‐binding transcription factor Fzf1. These results unveil a new genomic event that confers an evolutive advantage to wine yeast strains.